IMPLEMENTATION OF CERTAINTY FACTOR METHOD IN PEST AND DISEASE DIAGNOSIS IN HYDROPONIC PLANTS - Riski Afdhalis Syahreza; Jeperson Hutahaean; Afrisawati Afrisawati (Jurnal Teknik Informatika (Jutif), 2023)
Pest and disease attacks often occur in hydroponic plants so that many plants are damaged and result in losses for farmers or crop failure. The problem of pests and plant diseases is the main obstacle in increasing agricultural productivity, these conditions affect farmers' income and the provision of hydroponic plant food. The farmers do not know what types of pests and symptoms of diseases attack plants, making it difficult to handle diseases on hydroponic plants. Likewise for hydroponic plants located at the Agricultural Service of Asahan Regency which are attacked by pests, hydroponic experts say that the appearance of small leaf spots appears on the upper side of the leaves that damage hydroponic plants and because the cause of pests that cause disease in hydroponic plants is unknown, so farmers are hesitant to take countermeasures. An expert system is a computer program designed to make decisions such as decisions taken by an expert or expert. Therefore, an expert system with the Certainty Factor method is made in the diagnosis of pests and diseases in hydroponic plants. The purpose of this study was to apply the certanity factor method to diagnose pests and diseases in hydroponic plants. The results of the pest data test found spider mites with a confidence level of 79% and wet rot disease with a confidence level of 62%. The conclusion obtained is that the certainty factor method can detect early types of pests and diseases on hydroponic plants quickly and accurately.